Protective effects of intrathecal injection of AAV9-RabGGTB-GFP+ in SOD1G93A mice - Gao, Tianchu; Huo, Jia; Xin, Cheng; Yang, Jing; Liu, Qi; Dong, Hui; Li, Rui; Liu, Yaling (Frontiers in Aging Neuroscience, 2023)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease that widely affects motor neurons of the CNS. About 20% of patients with ALS have familial ALS (fALS). One of the classic models of ALS are SOD1G93A mice. Misfolded SOD1 protein can be overexpressed in motor neurons, which results in progressive paralysis of the limbs of mice. There is still no effective treatment for ALS. In recent years, the treatment of ALS by regulating autophagy has become a research hotspot. Autophagy obstacles have been confirmed to be one of the early pathological events of ALS. Rab7 is a member of the Ras superfamily and plays a key role in the late stage of autophagy. In our previous studies, we found that prenoylation of Rab7 was inhibited in the ALS model. Prenylation is a post-translational modification in which farnesyl or geranylgeranyl groups are covalently linked to target proteins. Based on these findings, we proposed the novel idea that the regulation of RabGGTB (the β-subunit of RabGGTase) mediated prenylation modification of Rab7, and that this can be used as a prevention and treatment of ALS associated with abnormal protein accumulation. In the present study, RabGGTB was overexpressed in mouse spinal cord motoneurons by using adeno-associated virus as vector. Our results show that the protein level of RabGGTB was significantly increased in the lumbar and thoracic regions of spinal cord motoneurons of injected mice. Furthermore, the onset time and survival time of SOD1G93A mice injected with AAV9-RabGGTB-GFP+ were delayed compared with those of mice without overexpression. At the same time, we also observed a decrease in SOD1 misfolded and glial overactivation in the lumbar spinal cord of these SOD1G93A mice. The findings reported here show that RabGGTB plays a significant role in the pathogenesis of SOD1G93A mice and with great therapeutic potential for reducing abnormal aggregation of SOD1 in ALS.